Improving Criminal Responsibility Determinations Using Structured Professional Judgment - Acklin, Marvin W.; Velasquez, Joseph P. (Frontiers in Psychology, 2021)
Forensic psychologists commonly utilize unstructured clinical judgment in aggregating clinical and forensic information in forming opinions. Unstructured clinical judgment is prone to evaluator bias and suboptimal levels of inter-rater reliability. Mechanical or actuarial predictive methods have been proposed as potential remedies. Following a review of canonical forensic assessment models, the prevalence of bias in forensic judgments, including adversarial allegiance, and inter-rater agreement in criminal responsibility determinations, this article presents a structured professional judgment (SPJ) model for criminal responsibility evaluations. A user-friendly methodology is described, applying procedural checklist, application of a mental state at time of the offense (MSO) model using structured data collection methods and mechanical (algorithmic) prediction, and post hoc hypothesis testing. A case study describes application of the procedural and criminal responsibility decision model in a complex homicide case.